Apnea Test - Seher Yanatma; Asu Özgültekin (Galenos Yayinevi, 2023)
Apnea test is among brainstem reflexes and performed to detect respiratory control. It has an important place in the diagnosis of brain death. Changes in vital signs, profound hypotension, and severe cardiac arrhythmias may occur during the apnea test, and intracranial pressure may increase markedly, so it should be performed after the other brain death tests were completed. It is a necessary test for diagnosis in cases where supportive tests cannot be performed. In this section, the pre-test conditions, the procedure, the difficulties encountered and the solution options are discussed.